AN ANALYSIS OF THE SHORTCOMINGS IN INTELLECTUAL PROPERTY RIGHTS PROTECTION AGAINST ARTIFICIAL INTELLIGENCE-BASED DIGITAL PLAGIARISM IN INDONESIA - Zulkifli; Nasrianti; Sofyan Jafar; Muhibuddin; Teuku Yudi Afrizal (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Advances in Artificial Intelligence (AI) technology have brought about significant changes in the digital creative industry, particularly in the production and distribution of digital content. AI-based systems are now capable of generating text, images, music, videos, and various other digital works quickly and on a massive scale. However, these technological advancements have also raised new legal issues in the field of Intellectual Property Rights (IPR), particularly regarding digital plagiarism through the unauthorized use of copyrighted works within AI systems. In practice, many AI systems utilize digital data and creative works without explicit consent from the original creators, potentially causing economic and moral harm to copyright holders. This study aims to analyze the weaknesses of intellectual property rights protection against digital plagiarism in the era of artificial intelligence in Indonesia and to evaluate the effectiveness of copyright regulations in addressing developments in digital technology. The study employs a normative legal research method using a legislative approach, a conceptual approach, and a case study approach. The legal materials consist of primary, secondary, and tertiary sources obtained through a literature review and analyzed qualitatively. Research findings indicate that intellectual property protection in Indonesia has not yet fully addressed the issue of AI-based digital plagiarism. Law No. 28 of 2014 on Copyright does not specifically address the legal status of works generated by AI, the limits on the use of digital data by AI systems, or the liability of AI developers for copyright infringement. Furthermore, weak digital oversight, rapid technological advancements, and the digital public’s limited legal understanding also impact the effectiveness of copyright protection in Indonesia.The novelty of this research lies in its analysis of the shortcomings of intellectual property protection in cases of AI-based digital plagiarism, as well as the urgent need for legal reform to create copyright regulations that are better adapted to advancements in modern digital technology.